Development of Monoclonal Antibodies against HIV-1 p24 Protein and Its Application in Colloidal Gold Immunochromatographic Assay for HIV-1 Detection. (16th March 2016) - Ma, Yi; Ni, Chao; Dzakah, Emmanuel E.; Wang, Haiying; Kang, Keren; Tang, Shixing; Wang, Jihua; Wang, Jufang
Abstract : Human immunodeficiency virus type 1 (HIV-1) p24 protein is the most abundant viral protein of HIV-1. This protein is secreted in blood serum at high levels during the early stages of HIV-1 infection, making it a biomarker for early diagnosis. In this study, a colloidal gold immunochromatographic assay (GICA) was established for detecting p24 protein using mouse monoclonal antibodies (mAbs). The HIV-1 p24 protein was expressed in E. coli strain BL21 and the purified protein was used to immunize mice. Stable hybridoma cell lines secreting anti-p24 monoclonal antibodies were obtained after ELISA screening and subcloning by limiting dilution. 34 different capture and labeling mAb pairs were selected by a novel antibody-capture indirect sandwich ELISA and then applied in GICA to detect p24 protein. The GICA method has a limit of detection (LOD) of 25 pg/mL and could detect p24 protein in all 10 positive samples obtained from the National Reference of HIV-1 p24 antigen. Out of 153 negative samples tested, 3 false positives results were obtained. The overall specificity of this test was 98.03%. The good sensitivity and specificity of this method make it a suitable alternative to provide a more convenient and efficient tool for early diagnosis of HIV infection.